Function of MAP kinases in plant signal transduction pathway networks - SONG Dong-hui; SONG Feng-ming; ZHENG Zhong (浙江大学学报. 农业与生命科学版)
Mitogen-activated protein kinase (MAPK) cascade, which consists of three Ser/Thr protein kinases, namely, MAP kinase kinase kinase, MAP kinase kinase and MAP kinase, is a universal module in signal transduction pathways in all eukaryotes. The MAPK cascades mediate the transmission of extracellular signals to the downstream effector proteins by a mechanism of sequential phosphorylation. In this review, we will summarize and discuss the recent progress in the role of MAPK cascades in signal transduction pathway networks in plant stress responses, disease resistance responses and hormone regulation.